Evaluation of Different Rates of Ampligo Insecticide against Fall Armyworm (Spodoptera frugiperda (JE Smith); Lepidoptera: Noctuidae) in the Coastal Savannah Agroecological Zone of Ghana - Michael Y. Osae; Justice O. Frimpong; Joshua O. Sintim; Benjamin K. Offei; Dinah Marri; Selorm E. K. Ofori (Advances in Agriculture)
The destructive nature of maize fall armyworm has triggered the importation of plenty of plant protection products onto the Ghanaian agrochemical marketplace. These imported chemicals sold at market places sometimes are unregistered for use in the Ghanaian environment. Thus, some importers do not do due diligence in testing the chemical agronomically to ascertain its mode of action and also being not harmful to beneficial insect species in the Ghanaian environment. It was in this view that three Ampligo concentrations or rates (0 ml/ha, 200 ml/ha, and 240 ml/ha) were tested against FAW on maize that were sown at a spacing of 60 cm × 60 cm. Treatments applied to maize were arranged in a randomised complete block design and replicated three times. Ampligo rates caused a very significant (p < 0.05) reduction in FAW at 21 and 28 days after maize emergence. The damage to maize leaf on treated maize plot was significantly (p < 0.05) different from that on the untreated. Thus, damage of FAW was more visible on maize leaves on control plots compared to the treated ones. A significantly (p < 0.05) positive correlation existed between damage rating and FAW number. Furthermore, the Ampligo rates correlated negatively to FAW density at p = 0.014 at 21 days after emergence. Also, FAW infestation did not impact maize grain yield. The study, therefore, concluded that Ampligo pesticide falls in low-risk plant protection product category with a very potent active ingredient that reduces FAW populations. We recommend that Ampligo should be applied between 14 and 21 days after emergence; two applications at one-week interval at 200 ml/ha are sufficient to sustain maize for the whole cropping season.